Função de PD-1 na apoptose de linfócitos T na leishmaniose visceral canina - Chiku, Vanessa Marim [UNESP] (2015)
Dogs infected with Leishmania infantum showed a reduction in the number of lymphocytes T. PD-1 (Programmed cell death 1) a new member of the B7-CD28 family, it is expressed by cells of the immune system and its binding to PD-L1 (CD274) or PD-L2 (CD273) induces deactivation of T cells or apoptosis. This study aimed to evaluate the PD-1 expression and its ligands as well as their role in T lymphocyte induction of apoptosis, TNF-α and IL-4 secretion, nitric oxide production and parasite load in dogs with visceral leishmaniasis. We observed that in canine visceral leishmaniasis PD-1 and its ligands involved in induction of apoptosis of T lymphocytes, are regulating the nitric oxide production, TNF-α, IL-4, as well as the parasitic load. This study helps to clarify the mechanism of immune response and immunotherapeutic drugs such as blocking monoclonal antibodies that can influence the LVC